Efektivitas Cacing Tanah Pheretima hupiensis, Edrellus sp. dan Lumbricus sp. dalam Proses Dekomposisi Bahan Organik - Ea Kosman Anwar (UNIVERSITY OF LAMPUNG, 2009)
Effectivity of the Earthworms Pheretima hupiensis, Eudrellus sp. and Lumbricus sp. on the Organic Matter Decomposition Process (E.K. Anwar): The earthworms are the one of soil fauna component in soil ecosystem have an important role in organic matter decomposition procces. The earthworm feed plant leaf and plant matter up to apart and dissolved. Earthworm metabolisms produce like faeces that mixed with decomposed organic matter mean vermicompost. The vermicompost fertility varies because of some kind of earthworm differ in “niche” and attitude. The experiment was to study the effectivity of earthworm on organic matter decomposition which has been conducted in Soil Biological and Healthy Laboratory and Green House of Soil Research Institute Bogor, during 2006 Budget Year. The three kind of earthworms i.e Pheretima hupiensis, Lumbricus sp. and Eudrellus sp. combined with three kind of organic matter sources i.e rice straw, trash and palm oil plant waste (compost heap). The result shows that the Lumbricus sp. are the most effective decomposer compared to Pheretima hupiensis and Eudrellus sp. and the organic matter decomposed by Lumbricus sp. as followed: market waste was decomposed of 100%, palm oil empty fruit bunch (compost heap) 95.8 % and rice straw 84.9%, respectively. Earthworm effectively decreased Fe, Al, Mn, Cu dan Zn.